2016
DOI: 10.1177/1526602815622433
|View full text |Cite
|
Sign up to set email alerts
|

AlluraClarity Radiation Dose–Reduction Technology in the Hybrid Operating Room During Endovascular Aneurysm Repair

Abstract: Changing a mobile C-arm for a fixed C-arm in a hybrid operating suite increased the average intraoperative dose during EVAR. Upgrading the Allura fixed C-arm with ClarityIQ technology resulted in a 61% reduction in the radiation per DSA frame.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 21 publications
2
29
0
Order By: Relevance
“…The disadvantage, however, is that the radiation dose is 3.5 times higher on average compared to mobile systems. 6,8,19 ClarityIQ is an imaging platform that is designed to address these issues. It utilizes reduced radiation dose settings, which inherently leads to decreased signal-to-noise ratio (SNR) of the images.…”
Section: Discussionmentioning
confidence: 99%
“…The disadvantage, however, is that the radiation dose is 3.5 times higher on average compared to mobile systems. 6,8,19 ClarityIQ is an imaging platform that is designed to address these issues. It utilizes reduced radiation dose settings, which inherently leads to decreased signal-to-noise ratio (SNR) of the images.…”
Section: Discussionmentioning
confidence: 99%
“…To address this issue, low-dose CTA protocols have been reported to show the feasibility of reducing both radiation dose (reduce tube voltage from 120 to 100 or 80 kV) and contrast volume (lower contrast medium to 30 mL) while capturing diagnostic-quality images. [46][47][48] Another strategy to solve this issue is to use duplex ultrasound as an alternative to CTA in the follow-up of EVAR patients. Several authors have shown that contrast-enhanced ultrasound is as accurate as or better than CTA in detecting endoleaks, monitoring aneurysm dimensional changes, and assessing stented vessel patency by analyzing hemodynamic flow to the renal arteries.…”
Section: Discussionmentioning
confidence: 99%
“…To address this issue, low-dose CTA protocols have been reported to show the feasibility of reducing both radiation dose (reduce tube voltage from 120 to 100 or 80 kV) and contrast volume (lower contrast medium to 30 mL) while capturing diagnostic-quality images. 4648…”
Section: Discussionmentioning
confidence: 99%
“…In an H-OR, an operating table is interconnected to a motorized flat panel detector C-arm with 2D/3D imaging, along with x-ray based image guidance tools. 10,11 In this study, we introduce an H-OR surgical navigation platform with optical cameras for augmented reality in intraoperative imaging and tracking. The optical platform was integrated with the standard flat detector frame of a motorized C-arm.…”
mentioning
confidence: 99%